Interpretation and Translation of Intertextual Meanings of Lithuanian Literature into French - Leonavičienė, Aurelija (Respectus Philologicus, 2013)
This article analyses the intertextual meanings of Lithuanian literature, how they are interpreted, and some tendencies of their translation into French. The material for the analysis comprises 27 Lithuanian literature novels and ten poems, together with their translations into French (published from 2000–2010). The analysis shows the tendencies of translation of intertextual meanings during the last decade. The results of the quantitative research indicate that intertextual meanings are mainly translated by proper names, meaningful word groups, and phrases. A dominant tendency when translating intertextual meanings into French is translation without changes, when the intertextual meaning is understood equivalently in both the source and target cultures, without the need for additional explanation. Other translation strategies (explicit rendering of intertextual meaning; wordfor-word translation or “internal emphasis”) were applied more rarely. Even though the examples of word-for-word translation comprise only one-fifth of all analysed intertextual meanings, the results of their analysis suggest that translators sometimes fail to choose appropriate translation strategies and translate the word forms of the intertextual units; in such cases, the translations lose important intertextual connections, intellectual and emotional connotations are neutralized, and the readers of the translation face “culture bumps.”
Keywords: Intertextual Meaning; Interpretation of Intertextual Meaning of Lithuanian Literature; Translation to French; Translation without Changes; Transference; Decontextualization; Explicit Rendering of Meaning